2019
DOI: 10.1016/j.jpeds.2019.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Use of a Decision Aid for Parents Facing Extremely Premature Delivery: A Randomized Trial

Abstract: Objective: To assess decisional conflict and knowledge about prematurity among mothers facing extreme premature delivery when the counseling clinicians were randomized to counsel using a validated decision aid compared with usual counseling. Study design:In this randomized trial, clinicians at 5 level III neonatal intensive care units (NICUs) in the United States were randomized to supplement counseling using the DA or to counsel mothers in their usual manner. We enrolled mothers with threatened premature deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 49 publications
0
23
0
2
Order By: Relevance
“…Guillen et al recently evaluated the use of a decision-making tool to inform parents with a high risk of extreme prematurity in order to investigate values and to ensure an informed parental decision concerning neonatal artificial life support. The authors observed that the use of this tool was related to greater understanding of complex information [ 21 ]. This kind of tool could be studied in the population with early-onset severe preeclampsia in order to explain maternal risks and perinatal survival and complications for joint parental and medical decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Guillen et al recently evaluated the use of a decision-making tool to inform parents with a high risk of extreme prematurity in order to investigate values and to ensure an informed parental decision concerning neonatal artificial life support. The authors observed that the use of this tool was related to greater understanding of complex information [ 21 ]. This kind of tool could be studied in the population with early-onset severe preeclampsia in order to explain maternal risks and perinatal survival and complications for joint parental and medical decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…It was modified and then embedded in a guideline, which was assessed in a qualitative study . It was also adapted into video format, translated into Spanish and tested in a randomised controlled trial (RCT) …”
Section: Resultsmentioning
confidence: 99%
“…Participants found DAs to be user‐friendly, understandable, acceptable and informative . Use of DAs was associated with increased knowledge, understanding and information recall and reduced decisional conflict . However, many parents viewed values clarification exercises as unclear, and some parents were unsure about the probabilities of complications .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…die sowohl für Entscheidungen in der Schwangerschaft als auch in Bezug auf die Behandlung extrem frühgeborener Kinder entwickelt wurden, [16][17][18][19], können Eltern helfen, komplexe Zusammenhänge besser zu verstehen. Sie entschärfen jedoch nicht den Entscheidungskonflikt [20,21]. Letztlich bildet der Dialog zwischen Ärztinnen und Ärzten einerseits und den Eltern andererseits, in dem die Sachkompetenz vornehmlich auf ärztlicher Seite, die Wertekompetenz vornehmlich bei den Eltern angesiedelt ist, das Kernstück einer gemeinsamen, partizipativen Entscheidungsfindung ("shared decision making") [22][23][24].…”
Section: Ethische Aspekteunclassified